Unusual Reactions of the 1,3-Dithiane Derivative of the Garner Aldehyde and Related Compounds - Philip, Anijamol T.; Chacko, Shibin; Ramapanicker, Ramesh (Synthesis, 2013)
Treatment of the 1,3-dithiane derivative of the Garner aldehyde with alkyl halides in the presence of n-butyllithium resulted in a ring-opening reaction to give differentially substituted propane-1,3-dithioethers, instead of the expected 2,2-dialkylated 1,3-dithiane products. The corresponding 1,3-dithiolane derivative also reacted in a similar manner. Such ring-opening reactions of dithiane or dithiolane derivatives are rare. A detailed study of this unusual reaction was carried out and a possible mechanism is proposed.
Keywords: dithianes; dithiolanes; butyllithium; ring opening; umpolung